STRATEGI IMPLEMENTASI PEMBELAJARAN PAK BERDASARKAN KURIKULUM MERDEKA DI SMKN 2 MANDREHE UTARA - Lay, Sergius; Ndoa, Paulinus Kanisius; Halawa, Rosaria Alami (IN VERITATE LUX, 2024)
This research departs from the concern over the reality of the implementation of the independent curriculum which is still not optimal, the difficulty of teachers in adjusting to the independent curriculum and inadequate facilities and infrastructure. The variables in this study consist of an independent curriculum, PAK learning and PAK learning implementation strategies based on an independent curriculum. The purpose of this study is to find out about the independent curriculum and PAK learning and the extent of the implementation of PAK learning based on the independent curriculum. The research method used is qualitative research with a case study approach. The sample selection in this study used purposive sampling technique. Data collection techniques were carried out using observation, interview and documentation techniques. Data validity testing is done by triangulation, namely data source triangulation and technical triangulation. Based on the research that has been carried out, the research results illustrate that the PAK learning implementation strategy based on the independent curriculum at SMK Negeri 2 Mandrehe Utara has strategies that include simplified lesson plans, provision of teaching tools, and more independent learning for teachers and students, so that learning is more enjoyable and meaningful. The independent curriculum has had a positive impact on SMK Negeri 2 Mandrehe Utara in the learning process, especially in PAK learning.